Desarrollo de una aplicación móvil (app) en e-learning como instrumento de apoyo educativo en tiempos de pandemia - Mezarina Mendoza, Jhon Paul Iakov (2022)
In the current context of virtual education, due to the health emergency caused by SARS-CoV-2, the development of technologies has been of great importance, constituting the ideal scenario for mobile applications (apps) aimed at higher education such as complement to academic activities. The objective of this article is to describe the process of creating an application (app) to complement an academic activity. This application may be used by both students and graduates of the dentistry career, facilitating and optimizing their academic activities. The application has been developed under the Mobile Development Process Spiral methodology, which follows the following order: First, exploration phase; second, initialization phase; third, production phase; fourth, stabilization phase and fifth, test phase. This mobile application expects to be evaluated in usability and satisfaction by the students and teachers who are our objective.